The association between preoperative anemia and postoperative morbidity in pediatric surgical patients: A secondary analysis of a prospective observational cohort study. Issue 7 (28th August 2020) - Meyer, Heidi M.; Torborg, Alexandra; Cronje, Larissa; Thomas, Jennifer; Bhettay, Anisa; Diedericks, Johan; Cilliers, Celeste; Kluyts, Hyla; Mrara, Busisiwe; Kalipa, Mandisa; Biccard, Bruce; ,
Abstract: Background: The prevalence of anemia in the South African pediatric surgical population is unknown. Anemia may be associated with increased postoperative complications. We are unaware of studies documenting these findings in patients in low‐ and middle‐income countries (LMICs). Aim: The primary aim of this study was to describe the association between preoperative anemia and 26 defined postoperative complications, in noncardiac pediatric surgical patients. Secondary aims included describing the prevalence of anemia and risk factors for intraoperative blood transfusion. Method: This was a secondary analysis of the South African Paediatric Surgical Outcomes Study, a prospective, observational surgical outcomes study. Inclusion criteria were all consecutive patients aged between 6 months and <16 years, presenting to participating centers during the study period who underwent elective and nonelective noncardiac surgery and had a preoperative hemoglobin recorded. Exclusion criteria were patients aged <6 months, undergoing cardiac surgery, or without a preoperative Hb recorded. To determine whether an independent association existed between preoperative anemia and postoperative complications, a hierarchical stepwise logistic regression was conducted. Results: There were 1094 eligible patients. In children in whom a preoperative Hb was recorded 46.2% had preoperative anemia. Preoperative anemia was independently associated with an increased risk of any postoperative complication (odds ratio 2.0, 95% confidence interval: 1.3‐3.1, P  = .002). Preoperative anemia (odds ratio 3.6, 95% confidence interval: 1.8‐7.1, P  < .001) was an independent predictor of intraoperative blood transfusion. Conclusion: Preoperative anemia had a high prevalence in a LMIC and was associated with increased postoperative complications. The main limitation of our study is the ability to generalize the results to the wider pediatric surgical population, as these findings only relate to children in whom a preoperative Hb was recorded. Prospective studies are required to determine whether correction of preoperative anemia reduces morbidity and mortality in children undergoing noncardiac surgery.